«Утка-Кролик» индустриального парка - Череватский, Д.Ю. (Економіка промисловості, 2016)
«Утка-Кролик» - бистабильная фигура Дж. Джастроу, ставшая для Т. Куна символом смены парадигмы, свойственной научной революции. Статья посвящена смене восприятия инвестиционной сути корпоративной разработки шахтного поля - прообраза индустриального парка подземного заложения (частная фирма, добывающая уголь в отводе государственной шахты, оказывающей фирме платные технологические услуги), реализованной в конце ХХ в. на шахте «Красноармейская-Западная» № 1 (ныне шахтоуправление «Покровское»). «Качка-Кролик» - бістабільне зображення, створене Дж. Джастроу, що стало для Т. Куна символом зміни парадигми, властивої науковій революції. Статтю присвячено зміні сприйняття інвестиційної суті корпоративної розробки шахтного поля - прообразу індустріального парку підземного закладення (приватна фірма, яка видобуває вугілля у відведенні державної шахти, що надає фірмі платні технологічні послуги), реалізованої в кінці ХХ ст. на шахті «Красноармійська-Західна» № 1 (нині шахтоуправління «Покровське»). The "Duck-Rabbit" is a bistable figure created by Joseph Jastrow, which for Thomas Kuhn has become a symbol of paradigm shift typical for scientific revolution. The article is devoted to the changes of perceptions of the investment essence of corporate development of mine field (Corporate Mine Development) which is the prototype of industrial park of underground location. In the 1990s mines of post-Soviet Ukraine were fully state-owned but budget subsidies to enterprises were discontinued. As a result, many mines were left without investment resources, and even without longwall equipment. It happened so at the new mine "Krasnoarmeyskaya-Zapadnaya" No. 1 (Donetsk Region). An original solution was found especially for that enterprise: the part of the state mine was transferred to the ownership of the private firm that possessed its own equipment to extract coal. And "Krasnoarmeyskaya-Zapadnaya" No. 1 as a public enterprise provided the firm with paid services such as transport and hoisting, power supply, ventilation, pumping, care about the personnel, etc. The new form of organization was called Corporate Mine Development. The analysis shows that the essence of the scheme is fundamentally different from the one that has been perceived during decades. Not the firm was the investor of the state enterprise as it was previously considered but the loss-making state mine acted as the investor of the profitable firm. This conclusion is based on the recognition that the long-term and regular tolling relationship between the company and the mine (in terms of transportation, hoisting, etc.) is a tool of informal redistribution and even expropriation of property as it is clear from the theory of recombination of ownership. The disclosure of tolling elements in the relationship of a state-owned coal enterprise and a firm extracting coal in its mine field has allowed classifying the mine as a subject that makes informal capital investments in the firm business. As Corporate Mine Development is a type of industrial park, the result may be useful for understanding the nature of the relationship of the park operating company with companies-participants.